2003
DOI: 10.1136/pmj.79.929.164
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study showing changes in the monthly incidence of Pneumocystis carinii pneumonia

Abstract: Pneumocystis carinii pneumonia (PCP) remains a serious opportunistic infection in HIV infected individuals. Seasonal changes in climate are associated with changes within individual susceptibility to infection. The possibility of monthly variability in the incidence of PCP was therefore examined by means of a cohort study of a database of 8640 HIV infected individuals attending the Chelsea and Westminster Hospital. There were 792 cases of PCP diagnosed since 1985. A marked decline was observed in the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The multivariate analysis (Table 2) demonstrated the following: (i) age at entry to cohort remained significantly associated with mortality, ages >39 having an increase in rate per year of increase in age (RR 1·03, 95% CI 1·02-1·03, P < 0·001); (ii) being female is associated with an increased mortality (RR 1·19, 95% CI 1·02-1·38, P = 0·028); (iii) T lymphocyte CD4 counts of <144 cells/mm 3 ( P = 0·001) and CD8 counts of less than 595 cells/mm 3 ( P = 0·001) were associated with an increased risk of death; (iv) nadir B cell CD19 counts <39 cells/mm 3 were associated with an increased risk of death (RR 1·41, 95% CI 1·18-1·67); and (v) decreased maximal HIV-1 viral loads, below the 75th centile of measured viraemia, was associated with protection from death (RR 0·85, 95% CI 0·73-0·98). When the parameters that approached significance were entered in a multivariate analysis, we found that low natural killer counts were not associated with death.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The multivariate analysis (Table 2) demonstrated the following: (i) age at entry to cohort remained significantly associated with mortality, ages >39 having an increase in rate per year of increase in age (RR 1·03, 95% CI 1·02-1·03, P < 0·001); (ii) being female is associated with an increased mortality (RR 1·19, 95% CI 1·02-1·38, P = 0·028); (iii) T lymphocyte CD4 counts of <144 cells/mm 3 ( P = 0·001) and CD8 counts of less than 595 cells/mm 3 ( P = 0·001) were associated with an increased risk of death; (iv) nadir B cell CD19 counts <39 cells/mm 3 were associated with an increased risk of death (RR 1·41, 95% CI 1·18-1·67); and (v) decreased maximal HIV-1 viral loads, below the 75th centile of measured viraemia, was associated with protection from death (RR 0·85, 95% CI 0·73-0·98). When the parameters that approached significance were entered in a multivariate analysis, we found that low natural killer counts were not associated with death.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…In those for whom it is available, highly active anti-retroviral therapy (HAART), consisting of at least three drugs, has decreased the morbidity and mortality associated with HIV, mainly by reducing the incidence of opportunistic infections such as Pneumocystis carinii pneumonia [1][2][3][4][5]. The protective effect of HAART has also been shown to result in a decreased incidence of HIV-associated cancers, including an increased time to disease progression [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, they could also be due to differences in population density, and in HIV infection or PcP incidence (Gal et al , 2010). On the other hand, several studies have shown seasonal changes of PcP incidence that seem to be associated with climate factors (Lubis et al , 2003; Varela et al , 2004; Sing et al , 2009). In this sense, the higher P. jirovecii colonization rates observed in patients with CF from Southern Europe than in patients from Northern Europe could be related with climate factors (Sing et al , 2001; Respaldiza et al , 2005; Gal et al , 2010).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Similar observations were made according to the climate of cities in the USA [6]. Only one study reported a correlation between low rainfall and new cases of pneumocystosis [8]. Navin et al 2000 indicated that outdoor activities such as gardening, camping or hiking were significantly associated with pneumocystosis in adults with human immunodeficiency virus [11].…”
Section: Resultsmentioning
confidence: 69%